Diseño de un Manual de Procedimientos para el Cumplimiento de las Obligaciones Tributarias de los Contribuyentes Pertenecientes al RIMPE, Ubicados en el Cantón Loja, periodo 2023 - Pineda Santórum, José Ignacio (2024)
The curricular integration work was developed with the purpose of designing a tax procedures manual with a logical and sequential order that facilitates the development of functions and activities for an adequate compliance with the payment of Income Taxes, in Popular and Entrepreneurial Businesses, subject to the RIMPE Regime. These manual details the steps to follow for the filing of returns, calculation, and payment of taxes, among other aspects related to tax regulations. In order to develop this work, in-depth research was carried out to obtain relevant information on the level of knowledge about tax procedures, to determine the current situation in which they are. In the tax area, policies and procedures focused on compliance with tax obligations were developed, with the objective of this manual is to facilitate compliance with tax obligations in a correct and timely manner, avoiding possible penalties for non-compliance. It also provides detailed information on the duties and rights of taxpayers, as well as the procedures to follow in the event of discrepancies or disagreements with the tax authority. Finally, tax flow charts were designed with the purpose of informing the owners and personnel, so that they can understand in a simpler and more effective way, step by step, the process to be followed on the procedures for each tax activity or operation. In the complementary part of this degree work, the conclusions with the respective recommendations are stated, which generate an important contribution of this work.